Antibacterial Activity of Liverworts of Dumortiera hirsute (Sw.) Nees Ethyl Acetate Extract Against Pathogenic Bacteria - Luthfiah, Luthfiah; Setyati, Dwi; Arimurti, Sattya (Universitas Jember, 2021)
Dumortiera hirsuta is one of the liverworts that can be used as a medicinal to prevent infection by pathogenic bacteria. The content of secondary metabolites of D. hirsuta has potential as antibacterial properties includes flavonoids, alkaloids and steroids. This research is to analyze the antibacterial activity of moss D. hirsuta against pathogenic bacteria that will be beneficial to humans. Liverworts of D. hirsuta were extracted using ethyl acetate solvent and tested against three types of pathogenic bacteria using the agar well-diffusion method. The results of this study indicated that the ethyl acetate extract of D. hirsuta at 100% concentration could inhibit the growth of Escherichia coli, Staphylococcus aureus, and Salmonella typhi bacteria. The range of antibacterial activity categories of the ethyl acetate extract of D. hirsuta to E. coli, S. aureus, and S. typhi between weak to moderate.